2002
DOI: 10.1038/nbt0502-508
|View full text |Cite
|
Sign up to set email alerts
|

Using the transcriptome to annotate the genome

Abstract: A remaining challenge for the human genome project involves the identification and annotation of expressed genes. The public and private sequencing efforts have identified approximately 15,000 sequences that meet stringent criteria for genes, such as correspondence with known genes from humans or other species, and have made another approximately 10,000-20,000 gene predictions of lower confidence, supported by various types of in silico evidence, including homology studies, domain searches, and ab initio gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
408
0
9

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(424 citation statements)
references
References 17 publications
7
408
0
9
Order By: Relevance
“…This makes SAGE useful as a gene discovery tool (Saha et al, 2002). In our study, approximately 5% of the tags (1918) were present in more than one library, but were unambiguously mapped to genomic regions outside any known genes.…”
Section: Discovery Of New Aging-related Genesmentioning
confidence: 69%
“…This makes SAGE useful as a gene discovery tool (Saha et al, 2002). In our study, approximately 5% of the tags (1918) were present in more than one library, but were unambiguously mapped to genomic regions outside any known genes.…”
Section: Discovery Of New Aging-related Genesmentioning
confidence: 69%
“…SAGE libraries were sequenced at random using a DNA sequencer (ABI PRISM 377; PE Biosystems, Foster City, CA, USA) and sequence kit (BigDye Terminator Cycle Sequence Kit; PE Biosystems). An NGT library was constructed with the original SAGE protocol (using ten base pair sequence tags), whereas the library for patients with type 2 diabetes was constructed with the long SAGE method (using 17 base pair sequence tags) [16]. Sequenced files were analysed with the SAGE 2000 software (http://www.sagenet.org).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the present method may enable RNAi-based forward genetics in which one can identify genes by selection based on absolute phenotypic criteria, such as cell morphology, adhesion, cell death, expression level of a key molecule or other functional indexes. shRNA sequences can serve as reliable tags for gene identification, because the probabilities of 9.1 × 10 -13 and 2.3 × 10 -13 that tags of 20 nt and 21 nt, respectively, with random sequences can be perfectly matched 25 are sufficiently small, considering the size of the mouse or human genome (∟3 × 10 9 nt).…”
Section: Discussionmentioning
confidence: 99%
“…We recovered shRNA constructs by PCR amplification from surviving cells and reconstituted them into retrovirus expression vectors to obtain the selected library. Relative reduction (25) To test whether the ganciclovir selection concentrated efficient shRNA constructs, we infected Jurkat T cells expressing GFP with a mixture of viruses prepared from the reconstituted library. Flow cytometry showed that GFP expression was more attenuated in cells transduced with retroviruses from the ganciclovir-selected library than in cells transduced with retroviruses from the untreated or parental library, indicating that ganciclovir selection concentrated the more efficient shRNA constructs (Fig.…”
Section: Selection Of Efficient Shrna Constructs In Cellsmentioning
confidence: 99%